2016
DOI: 10.1099/jmm.0.000285
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of meticillin-resistant Staphylococcus aureus bacteraemia using combined three-hour short-incubation matrix-assisted laser desorption/ionization time-of-flight MS identification and Alere Culture Colony PBP2a detection test

Abstract: Meticillin-resistant Staphylococcus aureus (MRSA) bloodstream infection is responsible for significant morbidity, with mortality rates as high as 60 % if not treated appropriately. We describe a rapid method to detect MRSA in blood cultures using a combined three-hour shortincubation BRUKER matrix-assisted laser desorption/ionization time-of-flight MS BioTyper protocol and a qualitative immunochromatographic assay, the Alere Culture Colony Test PBP2a detection test. We compared this combined method with a mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…To hasten this process, various purification and extraction methods have been developed recently to circumvent subculture step: these are generally manual methods based on abbreviated solid media culture ( Verroken et al, 2015 ; Delport et al, 2016 ), lysis-centrifugation ( Spanu et al, 2012 ; Foster, 2013 ), lysis-filtration ( Fothergill et al, 2013 ; Machen et al, 2014 ), serum separator tubes ( Barnini et al, 2015 ), or some combination of each ( Chen et al, 2015 ). Previous work with lysis-filtration methods showed similar ID results compared with lysis-centrifugation protocols even if the conditions of MALDI-TOF MS ID (e.g., adjustment of cut-off value in case of Bruker MS system) were not directly comparable.…”
Section: Introductionmentioning
confidence: 99%
“…To hasten this process, various purification and extraction methods have been developed recently to circumvent subculture step: these are generally manual methods based on abbreviated solid media culture ( Verroken et al, 2015 ; Delport et al, 2016 ), lysis-centrifugation ( Spanu et al, 2012 ; Foster, 2013 ), lysis-filtration ( Fothergill et al, 2013 ; Machen et al, 2014 ), serum separator tubes ( Barnini et al, 2015 ), or some combination of each ( Chen et al, 2015 ). Previous work with lysis-filtration methods showed similar ID results compared with lysis-centrifugation protocols even if the conditions of MALDI-TOF MS ID (e.g., adjustment of cut-off value in case of Bruker MS system) were not directly comparable.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we developed the npcRNA based detection using Sau-02 gene. Most of the detection studies carried out qualitatively to show the presence or absence of MRSA [ 36 , 39 , 40 ]. However, in our study we showed the detection level of genomic DNA equivalent to genome copies and whole cell MRSA as ~10 and 2 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This delay in definitive treatment reflects a delay in the identification and susceptibility profiling of S. aureus from positive blood cultures. The use of novel tools to identify S. aureus directly from blood cultures, such as fluorescence in situ hybridization (FISH), PCR, immunochromatographic assays for PBP2a, and other methods, has been shown to quickly and reliably identify S. aureus (Buchan et al, 2015;Delport et al, 2016;Felsenstein et al, 2016;Oliveira et al, 2002;Thomas et al, 2007). The use of such tools in the present setting could be valuable in encouraging prompt antimicrobial treatment of SAB and an improvement in patient outcomes, although cost may be an important limiting factor.…”
Section: Discussionmentioning
confidence: 99%